A REVIEW OF AUTHORIAL VOICE INTERVENTIONS AND RUBRICS: MAKING THE CASE FOR A MORE REFLEXIVE, STUDENT-FACING LEARNING TOOL - Jasbir Singh; Ben Daniel; Joyce Hwee Ling Koh (UICELL, 2021)
The development of authorial voice of university students in their academic writing is critical. This paper presents a summary and critical highlights of the pedagogical research, tools and interventions that aim to inculcate awareness and development of authorial voice in the academic writing of university students. The aim of this review is to make a case for a more student-facing and reflexive authorial voice learning tool. The paper argues that the majority of research and intervention that focuses in authorial voice stems from a researcher-facing or assessment perspective. The paper concludes by calling for a voice-specific learning tool that will attempt a more reflexive, student-facing approach to teaching novice student-writers about their authorial voice. Keywords: authorial voice, voice rubric